Controlled SBU Approaches to Isoreticular Metal‐Organic Framework Ruthenium‐Analogues of HKUST‐1. Issue 23 (17th July 2015) - Zhang, Wenhua; Kozachuk, Olesia; Medishetty, Raghavender; Schneemann, Andreas; Wagner, Ralph; Khaletskaya, Kira; Epp, Konstantin; Fischer, Roland A.
Abstract: A controlled secondary building unit approach (CSA) was employed to obtain a series of ruthenium metal‐organic frameworks (MOFs) of the general formula [Ru3 (BTC)2 X x ]· G g (BTC = 1, 3, 5‐benzenetricarboxylate; X = counter‐anion, G = guest molecules) which are structural analogues of [M3 (BTC)2 ] (M = Cu, Zn, Ni, Cr, Mo). The compounds [Ru2 (OOCR)4 X] and [Ru2 (OOCCH3 )4 ]Y were varied as Ru sources for CSA; namely strong coordinating X (Cl – ) and weakly coordinating Y ([BF4 ] – or [BPh4 ] – ) as well as the alkyl groups at the carboxylate ligand [R = CH3 or C(CH3 )3 ] were utilized. Four phase‐pure Ru‐MOFs were obtained: [Ru3 (BTC)2 Cl0.5 (OH)]· (AcOH)1.5 (1 ), [Ru3 (BTC)2 Cl1.2 (OH)0.3 ]· (H3 BTC)0.15 (AcOH)2.4 (PivOH)0.45 (2 ), [Ru3 (BTC)2 F0.5 (OH)]· (AcOH)1.0 (3 ) and [Ru3 (BTC)2 (OH)1.5 ]· (H3 BTC)0.5 · (AcOH)1.4 (4 ) AcOH = CH3 COOH, PivOH = (CH3 )3 CCOOH. The series of characterization data support the analytical composition and isostructural nature of1 –4, i.e. powder X‐ray diffraction (PXRD), IR‐ and 1 H‐NMR spectroscopy, thermal gravimetric analysis (TGA) and N2 sorption were employed. The valence state of the Ru‐sites were studied by X‐ray absorption spectroscopy (XAS). The chosen precursors for CSA and optimized synthesis, work‐up and activation protocols allowed improvement of the overall crystallinity, purity (i.e., residual solvent molecules) and surface area of the Ru‐MOF materials. Abstract : A controlled secondary building unit approach (CSA) was employed to obtain a series of isostructural ruthenium metal‐organic frameworks (MOFs) of the general formula [Ru3 (BTC)2 X x ]· G g (BTC = 1, 3, 5‐benzenetricarboxylate; X = counter anion, G = guest molecules) which are analogues of [Cu3 (BTC)2 ] (HKUST‐1).